An updated phylogeny of the human Y-chromosome lineage O2a-M95 with novel SNPs - Xiaoming Zhang (2018)
Though the Y-chromosome O2a-M95 lineage is one of the major haplogroups present in eastern Asian populations, especially among Austro-Asiatic speaking populations from Southwestern China and mainland Southeast Asia, to date its phylogeny lacks structure due to only one downstream SNP marker (M88) assigned to the lineage. A recent array-capturebased Y chromosome sequencing of Asian samples has yielded a variety of novel SNPs purportedly belonging to the O2a-M95 lineage, but their phylogenetic positions have yet to be determined. In this study, we sampled 646 unrelated males from 22 Austro-Asiatic speaking populations from Cambodia, Thailand and Southwestern China, and genotyped 12 SNP makers among the sampled populations, including 10 of the newly reported markers. Among the 646 males, 343 belonged to the O2a-M95 lineage, confirming the supposed dominance of this Y chromosome lineage in Austro-Asiatic speaking populations. We further characterized the phylogeny of O2a-M95 by defining 5 sub-branches: O2a1*-M95, O2a1a-F789, O2a1b*-F1252, O2a1b1*-M88 and O2a1b1a -F761. This updated phylogeny not only improves the resolution of this lineage, but also allows for greater tracing of the prehistory of human populations in eastern Asia and the Pacific, which may yield novel insights into the patterns of language diversification and population movement in these regions. © 2014 Zhang et al.